2019
DOI: 10.20396/bjos.v18i0.8656586
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the combination of Er:YAG laser and sandblasting on the shear bond strength between zirconia and resin cement

Abstract: Aim: This study was conducted to determine the bond strength between zirconia ceramic and resin luting cement according to the type of surface treatment applied. Methods: Sixty zirconia cylinders measuring 4 x 4 mm were manufactured and distributed into five experimental groups and a control group (n = 10): G1 - sandblasting with 110 μm aluminum oxide; G2 - sandblasting with 30 μm Rocatec Soft®; G3 - Er:YAG laser irradiation at 400 mJ; G4 - Er:YAG laser combined with sandblasting with aluminum oxide; G5 - Er:Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…J o u r n a l P r e -p r o o f and Nd:YAG laser [234,237,239,[241][242][243][244], conflicting results are frequently reported [245][246][247][248][249][250][251][252][253][254].…”
Section: Bonding Of Restorationsmentioning
confidence: 99%
“…J o u r n a l P r e -p r o o f and Nd:YAG laser [234,237,239,[241][242][243][244], conflicting results are frequently reported [245][246][247][248][249][250][251][252][253][254].…”
Section: Bonding Of Restorationsmentioning
confidence: 99%
“… 26 Subsequently, multiple studies have confirmed that laser engraving can significantly increase the SBS of Zr to DBRs or ICRs by creating micro-slits prior to bonding, which increases the surface area. 27 , 28 , 29 , 30 , 31 Accordingly, it is believed that laser engraving could improve the surface characteristics of PEEK, enhance mechanical bonding, and ultimately increase the SBS. 26 , 27 , 28 , 29 , 30 , 31 This study aims to evaluate the impact of grid-like microslits created by laser engraving on PEEK's surface and compare it with other mechanical surface treatments for bonding PEEK to DBRs or ICRs.…”
Section: Introductionmentioning
confidence: 99%
“… 27 , 28 , 29 , 30 , 31 Accordingly, it is believed that laser engraving could improve the surface characteristics of PEEK, enhance mechanical bonding, and ultimately increase the SBS. 26 , 27 , 28 , 29 , 30 , 31 This study aims to evaluate the impact of grid-like microslits created by laser engraving on PEEK's surface and compare it with other mechanical surface treatments for bonding PEEK to DBRs or ICRs. The null hypothesis of this study is that laser-engraved grid-like microslits do not significantly improve the shear bond strength of PEEK compared to other surface treatments.…”
Section: Introductionmentioning
confidence: 99%